Sviluppo e capitali delle medie imprese familiari italiane. I casi paradigmatici di The Bridge e Piquadro - Palazzi, Federica (Piccola Impresa / Small Business, 2011)
This research project does investigate the existing relation between the growth processes of Italian family medium-sized firms and the corresponding financing policies adopted. Two medium-sized firms, operating in the “made in Italy” sector, have been analysed, showing different financial approaches to promote the development process: one firm does use traditional financing tools (self-financing, commercial debts, short-term bank debts) and the other one does employ more developed financing tools (like private equity operator support or stock exchange quotation). The survey does allow to show some interesting variables that could explain the financial behaviour of medium-sized enterprises: objectives, preferences, past experiences, financial culture of the entrepreneur or entrepreneurial group, time and characteristics of the development project. The importance of each variables will be estimate in the future research project.